2014
DOI: 10.1007/s13277-014-2724-0
|View full text |Cite
|
Sign up to set email alerts
|

Crk-like adapter protein is required for TGF-β-induced AKT and ERK-signaling pathway in epithelial ovarian carcinomas

Abstract: Crk-like adapter protein (CrkL) was identified as an important biomarker in epithelial ovarian carcinomas. At the same time, the transforming growth factor β (TGF-β) pathway plays a key role in oncogenesis of advanced cancers. However, more detailed regulation mechanisms are still unclear. So we investigated the role of CrkL in TGF-β pathways in epithelial ovarian carcinomas. The small interfering RNA (siRNA) was used to suppress CrkL in serous papillary cystic adenocarcinoma (SKOV-3) cell line, TGF-β downstre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Because AKT phosphorylation is a hallmark of phosphatidylinositol 3-kinase (PI3K) activity, this finding indicates that Crk proteins are needed for LFA-1 dependent PI3K activation. In support of this idea, Crk proteins have been implicated in PI3K signaling in fibroblasts and transformed cells (4550).…”
Section: Resultsmentioning
confidence: 88%
“…Because AKT phosphorylation is a hallmark of phosphatidylinositol 3-kinase (PI3K) activity, this finding indicates that Crk proteins are needed for LFA-1 dependent PI3K activation. In support of this idea, Crk proteins have been implicated in PI3K signaling in fibroblasts and transformed cells (4550).…”
Section: Resultsmentioning
confidence: 88%
“…MAPK/ERK signaling is an important pathway that affects cell proliferation, and can be activated by growth factors such as TGF-β1 [26], [27], [28]. Because our data showed that GTP induced the expression of TGF-β1, we therefore examined the effect of GTP on ERK signaling pathway by Western blotting and immunofluorescence staining.…”
Section: Resultsmentioning
confidence: 99%
“…The stagnation of treatment is attributed to a lack of understanding of the PAH pathophysiological mechanisms and the absence of any efficacious drug against pulmonary vascular remodeling [4]. Recent studies have shown that the muscularization of nonmuscular pulmonary arterioles is a key characteristic of pulmonary vascular remodeling in PAH pathogenesis [59]. The new smooth muscle cells in muscularized nonmuscular pulmonary arterioles may originate from transdifferentiation and proliferation of pulmonary arterial endothelial cells (PAECs).…”
Section: Introductionmentioning
confidence: 99%